Perbedaan Kekuatan Geser Pelekatan Antara Resin Komposit Self Adhesive Flowable Dan Resin Komposit Dengan Bonding Self Etch pada Email Dan Dentin - , Anung Sri Gutomo; , drg. Pribadi Santosa, M.S., Sp. KG, ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The purpose of the study was to investigate the shear bond strength differences of self adhesive flowable and flowable resin composite with one step of self etch bonding either at enamel and dentin. Twenty caries free maxillary premolar teeth were prepared and fixed using self cure acrylic resin. All teeth were randomly assigned in four groups,each group consisted of five subjects. First group was applied with self adhesive flowable resin composite on enamel, while in second group was applied with self adhesive flowable resin composite on dentin.Third group was applied flowable resin composite with one step of self etch on enamel, while in fourth group was applied flowable resin composite with one step of self etch on dentin. Following immersion in artificial saliva for 24 hours at a temperature of 37°C, the teeth were thermocycled (4°C and 55°C each of 1 minute), then dried and tested using universal testing mechine. Data obtained were analyzed using two ways ANOVA. The statistical analysis using two ways ANOVA revealed that no different shear bond strength of resin composite using self adhesive flowable and flowable resin composite with one step self etch both on enamel and dentin (p>0,05). It can be concluded that there is no difference shear bond strength of resin composite using self adhesive flowable and flowable resin composite with one step self etch bond, there is no difference shear bond strength on the enamel and dentin and no interaction between type of flowable resin composite both enamel and dentin.